(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The aim of this study is to propose methods on research and analysis of interior spaces, by the means of sensor systems. The authors suggest quantitative observation of movement without other feedback from the occupant. The method is based on a system of sensors and technical solutions that was developed by the authors and is described in a patent with reg.№ 3895 U1 with authors Pavlina Vodenova, Desislava Angelova and Stela Tasheva. The proposal is meant to look into the dissatisfied and/or unanticipated in the environment project needs of the occupants and based on the data analysis, to offer optimization models.